Agricultural eco-efficiency and climate determinants: application of dea with bootstrap methods in the tropical montane cloud forests of Puebla, Mexico. Issue 1 (31st December 2022) - Rosano-Peña, Carlos; Pensado-Leglise, Mario Del Roble; Marques Serrano, André Luiz; Bernal-Campos, Aurelio Amado; Hernández-Cayetano, Marisol
ABSTRACT: This research analyzes the eco-efficiency of peasant production in a sample of 32 Puebla municipalities located in the tropical montane cloud forests (TMCF) and the influence of climatic factors, considering data from two years 2016–2017. Therefore, window data envelopment analysis approach with bootstrap in two stages was used. The results allow us to draw two basic conclusions. 1) It is possible, imitating the benchmarks, at the aggregate level in the region, to increase annual revenue and preserved areas by 58.7%, with the same inputs; or equivalently, reduce inputs and environmental costs by 36.98% with the same level of production. 2) Eco-efficiency scores are significantly affected by climatic factors and thus, the increase in temperature and the reduction in precipitation should have predominantly positive impacts on the region's eco-efficiency. This finding should be based on the characteristics of the region—humid mountainous forest with rain for most of the year and persistent mist almost at ground level. Based on this information, strategies can be defined by decision makers to harmonize economic growth and environmental preservation, as well as adaptive policies and actions to reduce vulnerability and improve the resilience of peasant producers.